Kemampuan Penyelesaian Masalah Matematis Siswa melalui Soal Cerita Deret Aritmatika dengan Tahapan Ideal: STUDENTS MATHEMATICAL PROBLEM SOLVING SKILLS THROUGH ARITHMETIC SEQUENCE WORD PROBLEMS WITH IDEAL STEPS - Marlinda, Marlinda; T, Ahmad Yani; Siregar, Nurfadilah; Meldi, Nadya Febriani (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
This research aims to describe the mathematical problem-solving abilities of students at SMAN 7 Pontianak regarding story problems in arithmetic sequences, based on the IDEAL stages. The subjects of this study were selected based on their categorization into high, medium, and low ability students. This research employed a descriptive approach with qualitative methods. The instruments used for data collection included problem-solving ability test results and interview sheets.The findings of the study indicate that: (a) subjects with high problem-solving abilities successfully completed all five stages of the IDEAL problem-solving process. (b) subjects with medium problem-solving abilities were able to perform the IDEAL stages, but their results still contained errors. (c) subjects with low problem-solving abilities struggled to complete all five IDEAL stages when solving story problems in arithmetic sequences. Students with lower academic performance were only able to identify problems. They faced difficulties in defining goals and exploring possible strategies, which led to mistakes in the subsequent stages.